2018
DOI: 10.1177/1090198118759148
|View full text |Cite
|
Sign up to set email alerts
|

Peer Crowd Identification and Adolescent Health Behaviors: Results From a Statewide Representative Study

Abstract: Findings from the first representative study of peer crowds and adolescent behavior identify two high-risk groups, providing critical insights for practitioners seeking to maximize public health interventions by targeting high-risk crowds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 29 publications
6
43
1
Order By: Relevance
“…For traditional, mass-reach tobacco public education campaigns, high campaign awareness and positive receptivity to ads in the first year of a campaign are early indicators of success,23 25–27 30 35 but benchmarks are unavailable for primarily digital campaigns like This Free Life . This evaluation will therefore be important in contributing to a larger body of knowledge in the establishment of benchmarks for future digital campaigns targeting peer crowds with higher risk of tobacco use (eg, Jordan et al ,36 Moran et al 14 and Walker et al 37).…”
Section: Discussionmentioning
confidence: 99%
“…For traditional, mass-reach tobacco public education campaigns, high campaign awareness and positive receptivity to ads in the first year of a campaign are early indicators of success,23 25–27 30 35 but benchmarks are unavailable for primarily digital campaigns like This Free Life . This evaluation will therefore be important in contributing to a larger body of knowledge in the establishment of benchmarks for future digital campaigns targeting peer crowds with higher risk of tobacco use (eg, Jordan et al ,36 Moran et al 14 and Walker et al 37).…”
Section: Discussionmentioning
confidence: 99%
“…4 Research has consistently found several overarching domains of peer crowds among adolescents, 2,5 each with relatively consistent profiles of risk behavior. 6 Crowds include mainstream, social, alternative, hip hop, and country. 2,3,6 Table 1 presents descriptions of common adolescent crowds and associated substance use behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the 'Social Screens' segment may be at higher risk of inactivity during adulthood, as there is some evidence that PA participation during adolescence may track into adulthood [31]. This segment also has a similar profile to the high-risk 'alternative' peer subculture described by Jordan and colleagues [32] as taking pride in being different from the 'mainstream' [32] and being sceptical of overt health promotion approaches [33]. Although the 'Social Screens' segment is relatively small, it may be viewed as a niche subgroup that might be difficult to reach with broadly-targeted health promotion approaches [34].…”
Section: Discussionmentioning
confidence: 68%